Biochemical impact of soccer: an analysis of hormonal, muscle damage, and redox markers during the season - Silva, J. R.; António Rebelo, A.; Marques, F.; Pereira, L.; Seabra, A.; Ascensão, A.; Magalhaes, J. (Applied Physiology, Nutrition, and Metabolism, 2014)
This study aimed to analyze changes in performance, muscle function, and stress-related biochemical markers in professional soccer players (n = 14) at 4 timepoints (3 for performance and 4 for stress-related biochemical markers) during the soccer season preseason (E1), midseason (E2), end of the season (E3) and after the end of the recovery period (E4). Performance in 5- and 30-m sprints, countermovement jump, and agility, and maximal isokinetic knee extension and knee flexion strength were measured (E1 to E3). We observed increased in-season levels of myoglobin (E2 > E1 and E4; p < 0.05), a higher testosterone/cortisol ratio (T/C), and increased levels of creatine kinase (CK), C-reactive protein, superoxide dismutase (SOD), protein sulfhydryls (-SH), and malondialdehyde (E2 and E3 > E1 and E4; p < 0.05). Lower cortisol concentrations (E3 < E1 and E4; p < 0.05) and glutathione reductase activity (E3 < E2 and E4; p < 0.05) were observed at the end of the season. T/C, CK, SOD, -SH, and malondialdehyde decreased during the off-season, and cortisol and glutathione reductase increased (E3 < E4; p < 0.05). Agility increased in E2 and E3 (p < 0.01). Significant correlations were found during the season between hormonal and muscle function parameters (r = 0.56-0.86; p < 0.05). In addition, in E2, significant associations were observed between match-accumulated time (MATE2; minutes played by each player during the competition period), performance, and hormonal and redox parameters (r = 0.456-0.615; p < 0.05). In conclusion, this study shows that soccer players face significant changes in biomarkers of physiologic strain (muscle damage and oxidative stress-related markers) during the season, but values return to normal during the off-season. Additionally, MAT influences physical, hormonal, and oxidative stress-related parameters in professional soccer players.